2007
DOI: 10.1086/512681
|View full text |Cite
|
Sign up to set email alerts
|

Interruption of Antiretroviral Treatment in HIV‐Infected Patients with Preserved Immune Function Is Associated with a Low Rate of Clinical Progression: A Prospective Study by AIDS Clinical Trials Group 5170

Abstract: Disease progression after TI was low in this cohort. A higher nadir in CD4(+) cell count, a lower HIV load before ART, and an HIV load < or =50 copies/mL at the time of TI predicted a longer time to the primary end point.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
76
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(85 citation statements)
references
References 40 publications
8
76
1
Order By: Relevance
“…However, ART alone is unable to eradicate infected cells, and without lifelong treatment, HIV plasma viremia almost invariably rebounds (2,3). One study of individuals undergoing multiple short ATIs detected generally homogeneous populations of rebounding virus with different lineages present at different ATI cycles, suggesting stochastic reactivation of monoclonal or small oligoclonal populations of latently infected cells (4).…”
Section: Importancementioning
confidence: 99%
“…However, ART alone is unable to eradicate infected cells, and without lifelong treatment, HIV plasma viremia almost invariably rebounds (2,3). One study of individuals undergoing multiple short ATIs detected generally homogeneous populations of rebounding virus with different lineages present at different ATI cycles, suggesting stochastic reactivation of monoclonal or small oligoclonal populations of latently infected cells (4).…”
Section: Importancementioning
confidence: 99%
“…Participants in 6 ACTG ATI studies (ACTG 371 [18], A5024 [19], A5068 [20], A5170 [21], A5187 [22], and A5197 [23]) were included if they were on suppressive ART, received no immunologic interventions (e.g., therapeutic vaccination, IL-2), and had HIV-1 RNA <50 copies/mL at the time of ATI. For participants of ACTG 371, A5024, A5068, and A5197, viral loads were measured at ATI weeks 1, 2, 3, 4, 6, 8, 10, 12, and 16.…”
Section: Study Populationmentioning
confidence: 99%
“…8,9 There are conflicting results as to whether these patients can safely discontinue ART. [10][11][12] Studies have shown that cognitive deficits are associated with ongoing viral replication in the CNS and that neurocognitive functioning improves in patients who initiate ART. [13][14][15][16][17][18] This recovery of function suggests that the underlying mechanism includes an alteration of neuronal function prior to actual cell death.…”
mentioning
confidence: 99%
“…11 In step 1, eligible subjects elected to stop antiretroviral therapy; in step 2, patients from step 1 reinitiated antiretroviral therapy. This study design provided a Class III level of evidence.…”
mentioning
confidence: 99%